2016
DOI: 10.3390/cli4010010
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Trend Analysis of Precipitation and Air Temperature for Kentucky, United States

Abstract: Variation in quantities such as precipitation and temperature is often assessed by detecting and characterizing trends in available meteorological data. The objective of this study was to determine the long-term trends in annual precipitation and mean annual air temperature for the state of Kentucky. Non-parametric statistical tests were applied to homogenized and (as needed) pre-whitened annual series of precipitation and mean air temperature during 1950-2010. Significant trends in annual precipitation were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 50 publications
0
53
0
Order By: Relevance
“…Parametric and nonparametric approaches are commonly used for identifying trends in hydrological and meteorological variables across the world (Ficklin et al 2013;Chattopadhyay and Jha 2016;Chattopadhyay and Edwards 2016). The Mann-Kendall (MK) and modified MannKendall (MMK) tests belong to the family of nonparametric tests.…”
Section: Trend Detection Methods Applied In the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Parametric and nonparametric approaches are commonly used for identifying trends in hydrological and meteorological variables across the world (Ficklin et al 2013;Chattopadhyay and Jha 2016;Chattopadhyay and Edwards 2016). The Mann-Kendall (MK) and modified MannKendall (MMK) tests belong to the family of nonparametric tests.…”
Section: Trend Detection Methods Applied In the Studymentioning
confidence: 99%
“…Numerous studies have employed the MK (Chattopadhyay and Edwards 2016;Tosunoglu and Kisi 2016) and MMK (Giuntoli et al 2013;Kibria et al 2016). These are possibly the most widely used nonparametric tests for trend detection in hydrological and climatological studies (Mitof and Pravalie 2014;Jones et al 2015).…”
Section: Trend Detection Methods Applied In the Studymentioning
confidence: 99%
“…The missing data were reconstructed by calculating the average value of their neighboring stations [15,25]. Considering relocation and instrument changes of meteorological stations, which may lead to implausible or biased conclusions, the double-mass curve method was adopted to detect the homogeneity of the meteorological data for each station in this study [15,[26][27][28]. After these procedures, 17 rain gauges and nine meteorological stations were retained for the subsequent trend analysis.…”
Section: Data Acquisition and Processingmentioning
confidence: 99%
“…The serial correlation analysis method presented by Yue et al [36] was used to test the presence of serial correlation proposed. Lag-1 serial correlation test was analyzed according to proposal from von Storch [38] and was adopted widely to eliminate the effect of serial correlation [27,28,39,40]. In this study, a trend-free pre-whitening (TFPW) method was used as follows:…”
Section: Serial Correlation Effectmentioning
confidence: 99%
“…Addisu et al, (2015) [24] found that MK trend test gave the maximum and minimum temperature analysis resulted in a general increasing trend whereas, rainfall amount resulted in a general decreasing trend in Ethiopia. Chattopadhyay and Edwards (2016) [25] analysed the long-term trends in annual precipitation and mean annual air temperature (for the period 1950-2010) for the state of Kentucky.…”
Section: Introductionmentioning
confidence: 99%